Thermal performance characteristics of liquid sodium as a coolant flowing past a rectangular nuclear fuel element. (2016) - Kaladgi, Abdul Razak; Samee, A.D. Mohammed; Ramis, M.K.
The objective of this work is to numerically investigate the effect of various design parameters on the steady state thermal performance characteristics of liquid sodium which flows as a coolant over a rectangular nuclear fuel element having non-uniform volumetric energy generation. Accordingly, the stream function-vorticity formulation of the full Navier Stokes equations governing flow and thermal fields in the fluid domain (coolant) are solved simultaneously along with energy equation of fuel element, using finite difference schemes. The results obtained are presented in the form of variation of mean coolant temperature at the exit, average Nusselt number and average skin friction coefficient for a wide range of parameters - aspect ratio, Ar, conduction-convection parameter Ncc, total energy generation parameter Qt, and flow Reynolds number ReH . It is concluded that out of the various parameters studied, the flow Reynolds number, ReH considerably influences the mean exit temperature, whereas Ar has the least influence on it.